(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Orthogonal Frequency Division Multiplexing (OFDM) is predicted to be implemented in future broadcasting and Wireless Local Area Network (WLAN) systems due to its robustness in transmitting a high data rate. With the rapid growth of digital communication in recent years the need for higer speed data transmission is increased. OFDM is a one solution for achieving high data rates in mobile environments, due to its resistance to ISI, which is a common problem found in high speed data communication. A multiple-input multiple-output (MIMO) communication System combined with the orthogonal frequency division multiplexing (OFDM) modulation technique can achieve reliable high data rate transmission over broadband wireless channels. In this paper explains the performance of MIMO OFDM under the AWGN Channel, Rayleigh channel, Rician Channel and Nakagami Channel also it uses different guard interval with modulation schemes as 4-QAM, 8-QAM, 16-QAM ad 32-QAM. It shows that by using OFDM with MIMO, The performance of MIMO- OFDM is evaluated on the basis of Bit Error Rate (BER)